Paper-based LRET sensor for the detection of total heavy rare-earth ions - Chen, Qiang; Tang, Keren; Luo, Dengwang; Han, Luodan; Yu, ChunXiao; Shen, Yiping; Lin, Qi; Chen, Yiting; Li, Chunyan; Chen, Jinghua; Lan, Jianming (Frontiers in Chemistry, 2022)
Based on the mechanism of luminescence resonance energy transfer (LRET) and using a special single strand DNA as the recognition element, a portable paper-based sensor for the accurate detection of total heavy rare-earth ions (mainly Gd3+, Tb3+ and Dy3+) concentration was proposed. The RNA cleaving-DNAzyme should recognize rare-earth ions to cleave RNA on DNA duplexes linking UCNPs and AuNPs, causing UCNPs and AuNPs to approach each other, inducing LRET, which attenuated the green upconversion luminescence (UCL) triggered by the 980 nm laser. UCL was captured by a charge-coupled device (CCD) image sensor and processed with the red-green-blue (RGB) image to quantitatively analyze heavy rare-earth ions in the samples. In the range of 5 to 50 μmol•L-1, the sensor has good sensitivity, with the limit of detection of 1.26 μmol•L-1.